INTERNATIONAL HUMAN RIGHT AND ISLAMIC LAW: Sebuah Upaya “Menuntaskan” Wacana-Wacana Kemanusiaan - Mukhlis, Febri Hijroh (IAIN Ponorogo, 2017)
Abstract: Islam offers eternal universal message, namely justice, equality, respect and humanity. This universal message is the holy Sunnah of the Prophet. Due to the advanced information and technology, the current problems of mankind increasingly appear. The problem can be viewed positively if everyone understands completely the universal message of prophethood by always stand in the social-humanity. This articleis intended to examine the issue of human rights and Islamic law as an effort to end the dichotomy between Islam and humanitarian problems. It employed descriptive qualitative study that concern with a conceptual disputes. The findings showed that the dichotomy between the concept of human rights and Islamic law must be completed in terms of equality and humanity. Humanitarian affairs are a common action regardless of any interests, religion, politics, culture and even knowledge. If the harmony and understanding between the concept of humanity in the religious or tauhid framework is absence, the understanding of humanity must be freed from all forms of identity interest. Islamic law and human rights are two matters that support each other. Islam respects human rights and vice versa. The religious view must be universal as the views of human rights should also be universal. Each restricted view narrows the relationship. كان الإسلام يحمل رسالة عالمية وهي العدالة والمساواة والاحترام والإنسانية. ملخص:وهذه الرسالة العالمية في الواقع من السنة النبوية المقدسة. ولكن الآن هناك مشكلات متنوعة يواجهها الإنسان فى عصر المعلومات والتكنولوجيات. وهذه المشكلات يمكن أن تكون إيجابية إذا كان الإنسان يفهم حقوق الرسالة النبوية العالمية التي تميل دائما إلى مجال الاجتماعية-الإنسانية. تبحث هذا البحث فى دراسة قضية حقوق الإنسان والشريعة الإسلامية كالمحاولة لإنهاء التناقض بين الشريعة والإنسانية. هذه المقالة من البحث النظري باستخدام الدراسة النوعية الوصفية. وخلاصة هذه المقالة أن ليس هناك التناقض بين مفهوم حقوق الإنسان والشريعة الإسلامية لأن أهدافها متساوية وهي العدالة والمساواة والإنسانية. ومن الممكن حل المشكلات الإنسانية تحت رعاية الشريعة الإسلامية والإنسانية بدون النظر إلى أية دين، وسياسة، وثقافة، ومعرفة. وإذا كان هناك التناقض بين مفهوم الإنسانية والشريعة الإسلامية فيجب أن تقدّم الإنسانية براءة من أية علاقة الهوية. إن الشريعة الإسلامية وحقوق الإنسان فى الحقيقة أمران يدعمان بعضهما بعضا. الإسلام يحترم حقوق الإنسان وكذلك العكس. ويجب أن تكون الفكرة الدينية عالمية وكذلك آراء حقوق الإنسان فينبغي أن تكون عالمية أيضا. الفكرة الضيقة لكل منها ستحمل إلى العلاقة الضيقة بينها. Abstrak: Islam membawa pesan universal yang abadi, yakni, keadilan, persamaan, penghargaan dan kemanusiaan. Pesan universal inilah sebenarnya Sunnah Nabi yang suci. Namun problem terkini umat manusia begitu variatif, degan semakin majunya informasi dan teknologi. Problem tersebut bisa menjadi positif jika semua orang benar-benar memahami pesan universal kenabian dengan selalu memihak kepada sosial-kemanusiaan. Artikel ini berupaya mengkaji problem HAM dan hukum Islam sebagai salah satu upaya untuk mengakhiri dikotomi antara Islam dan problem kemanusiaan. Artikel ini merupakan kajian konseptual, dengan jenis kajian kualitatif deskriptif. Kesimpulan dari kajian ini yaitu, dikotomi antara konsep HAM dan hukum Islam haruslah dituntaskan, kedunya pada satu ujung tujuan, yakni keadilan, kesetaraan dan kemanusiaan. Urusan kemanusiaan adalah urusan bersama tanpa memandang kepentingan apapun, baik agama, politik, budaya, bahkan pengetahuan. Jika tidak adanya keharmonisan dan kesepahaman antara konsep kemanusiaan dalam bingkai keagamaan atau tauhid maka pemahaman tentang kemanusiaan haruslah dibebaskan dari segala bentuk kepentingan identitas. Hukum Islam dan HAM adalah dua hal yang saling mendukung. Islam menghargai HAM begitupun sebaliknya. Pandangan agama haruslah bersifat universal sebagaimana pandangan mengenai HAM juga sebaiknya bersifat universal. Pandangan masing-masing yang sempit akan menyempitkan hubungan keduanya pula. Keywords: international human right, Islamic law, humanity